Knowledge on Puerperal Sepsis among Hospitalized Postnatal Mothers in a Lumbini Provincial Hospital - Kausal, Sabita; Dangol, Bhuwan Kumari (Journal of Nursing Education of Nepal, 2022)
Introduction: Puerperal sepsis is a leading cause of maternal mortality and morbidity in developing  countries due to the lack of knowledge on preventive measures. The objective of the study was to find  out the knowledge on puerperal sepsis among hospitalized postnatal mothers.  Method: A descriptive cross-sectional research design was adopted among 262 postnatal mothers who  were admitted in Lumbini Provincial Hospital. Data were collected by using non-probability purposive  sampling technique, through structured interview schedule. Data was analyzed by using descriptive  and inferential statistics. Result: More than one third of respondents (38.2%) were from the age group 25-29 years with mean  age was 26.21+4.44. Only 19.1% had good level of knowledge on puerperal sepsis.There was statistical  association between level of knowledge on puerperal sepsis and ethnicity (p=0.006), educational level  (p
Keywords: Knowledge; Postnatal mother; Post-partum Period; Puerperal sepsis